2011
DOI: 10.1038/labinvest.2010.148
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and HSC-specific sorafenib effects in rats with established secondary biliary cirrhosis

Abstract: Portal hypertension in cirrhosis depends on increased intrahepatic vascular resistance, which is explained by fibrosis and intrahepatic hyperresponsiveness to vasoconstrictors. Both are caused by activation and proliferation of hepatic stellate cells (HSCs). Portal hypertension of cirrhotic rats can be reduced by the multikinase inhibitor sorafenib, due to a reduction of intrahepatic vascular resistance. Therefore, the hepatic effects of sorafenib require further understanding. Here, we investigated hepatic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…Mejias et al first reported sorafenib ameliorated portal hypertension, intrahepatic fibrosis, inflammation, and angiogenesis in a cirrhotic rat model (19). Subsequent studies demonstrated sorafenib might reduce HSC proliferation, and inhibit the synthesis of fibrogenesis-related proteins and extracellular matrix (7,20,21). Sorafenib inhibits the KLF6/angiopoietin-1/fibronectin to disrupt the LSEC-HSC interactions, affecting the matrix reconstruction and vascular remodeling (22).…”
Section: Discussionmentioning
confidence: 99%
“…Mejias et al first reported sorafenib ameliorated portal hypertension, intrahepatic fibrosis, inflammation, and angiogenesis in a cirrhotic rat model (19). Subsequent studies demonstrated sorafenib might reduce HSC proliferation, and inhibit the synthesis of fibrogenesis-related proteins and extracellular matrix (7,20,21). Sorafenib inhibits the KLF6/angiopoietin-1/fibronectin to disrupt the LSEC-HSC interactions, affecting the matrix reconstruction and vascular remodeling (22).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted in this regard that previous attempts at targeting angiogenesis in cirrhosis by using multikinase inhibitors, such as sorafenib or imatinib, were successful in rats,5 6 but have little translational potential due to the many adverse effects that these agents may have by interfering with physiological angiogenesis 8 9. In fact, it has been previously reported that sorafenib at doses of 60 mg/kg induced biochemical and histological signs of liver injury, especially in cirrhotic rats 28. Our studies, therefore, provide in vivo evidence suggesting that exogenous PEDF supplementation may be a promising and plausible therapeutic modality for treatment and prevention of PH and chronic liver disease, at least in an early clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Some adverse effects of anti-angiogenesis therapy in cirrhotic patients have been reported, including interstitial pneumonitis and variceal bleeding [38,39]. In addition, Henneberg et al demonstrated that 7 days of sorafenib treatment [60 mg·(kg of body weight) − 1 ·day − 1 ] caused impaired liver biochemistry and damaged hepatic histology in CBDL rats [40]. They found that sorafenib-induced hepatic injury in both CBDL and sham-operated rats, but worse in CBDL rats, which implicated that high-dose sorafenib treatment may have direct hepatic toxicity in cirrhotic rats [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Henneberg et al demonstrated that 7 days of sorafenib treatment [60 mg·(kg of body weight) − 1 ·day − 1 ] caused impaired liver biochemistry and damaged hepatic histology in CBDL rats [40]. They found that sorafenib-induced hepatic injury in both CBDL and sham-operated rats, but worse in CBDL rats, which implicated that high-dose sorafenib treatment may have direct hepatic toxicity in cirrhotic rats [40]. It is noteworthy that the regimen of 14 days of sorafenib treatment [10 mg·(kg of body weight) − 1 ·day − 1 in the present study] elevates the plasma levels of AST and ALT in sham-operated rats.…”
Section: Discussionmentioning
confidence: 99%